The perception of the bearers of Diabetes Mellitus type 2 in relation to amputation - Lucas, Lúcia Percília Pereira (2010)
This paper is a descriptive study with qualitative and hermeneutics. It aims to describe the perception of patients with type 2 of diabetes in relation to their amputation and expectations for the future. Data were collected with seven subjects through the application of a semi-structured questionnaire. After analyzing the results, we learned that to go through an amputation may generate feelings of sadness and relief. The expectations post-amputation sub-themes emerged from dependence to daily activities, the religious attachment and fear of reviving a new amputation. It was noted the importance of nurses in the provision of a humanized patients underwent an amputation as well as providing educational activities for self-care to patients with Type 2 of diabetes mellitus to the changes resulting from the amputation.